2017
DOI: 10.1161/circresaha.117.311312
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Event Prediction by Machine Learning

Abstract: Rationale Machine learning may be useful to characterize cardiovascular risk, predict outcomes and identify biomarkers in population studies. Objective To test the ability of random survival forests (RF), a machine learning technique, to predict six cardiovascular outcomes in comparison to standard cardiovascular risk scores. Methods and Results We included participants from the Multi-Ethnic Study of Atherosclerosis (MESA). Baseline measurements were used to predict cardiovascular outcomes over 12 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
291
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(310 citation statements)
references
References 31 publications
12
291
2
5
Order By: Relevance
“…The phenomenon can also be seen in other studies. In one recent study predicting cardiovascular events using machine learning, a model with top‐20 variables was also used and showed excellent performance compared with a model with all variables . In addition, as the top variables mostly contributed to the model, it was shown that a model with only nine variables (forwardly selected) had better performance than a model with all variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon can also be seen in other studies. In one recent study predicting cardiovascular events using machine learning, a model with top‐20 variables was also used and showed excellent performance compared with a model with all variables . In addition, as the top variables mostly contributed to the model, it was shown that a model with only nine variables (forwardly selected) had better performance than a model with all variables.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine‐learning methodologies have emerged in medical prediction models, especially in cardiovascular disease . In a similar way, this new approach might improve the performance of current fracture prediction models by including all possible variables such as the BMD of all sites as well as trabecular bone score (TBS) data.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, machine learning techniques have emerged as highly effective methods for prediction and intelligent decision-making in many areas of everyday living [15; 16]. Recently machine learning applied to medical imaging has shown to improve diagnostic accuracy [17; 18] and prognostic outcomes [19; 20]. The aim of this study was to investigate if lesion-specific ischemia by FFR can be effectively predicted by machine learning integration of quantitative plaque metrics measured from CTA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be more accurate than the ECG in detecting transient episodes like myocardial ischaemia [107]. It is a rich source of data but is, by far, less commonly used and accessible than standard ECG.…”
Section: Discussionmentioning
confidence: 99%